Economic burden and influence factors among hospitalized children with bronchiolitis or pneumonia: a multiregional study in China - Hu, Hongfei; Zhou, Ting; Gao, Junyang; Ou, Yanglu; Ma, Aixia; Wang, Pei (Frontiers in Public Health, 2024)
Background: Bronchiolitis and pneumonia are both significant lower respiratory tract infections with a profound impact on children's health. The purpose of this study is to explore the economic burden and related influence factors of pediatric patients with bronchiolitis and pneumonia in China. Methods: A face-to-face interview was employed for the investigation of hospitalized patients (≤5 years old) with bronchiolitis and pneumonia, along with their guardians from January to October 2019. Demographic and costs were collected from Shanghai, Zhengzhou, and Kunming, representing three regions with different levels of economic development in China. Multiple linear regression analysis was used to explore factors associated with the economic burden of the diseases. Results: A total of 338 patients with bronchiolitis and 529 patients with pneumonia were included in the analysis. The average hospitalization and total cost for patients with bronchiolitis are 4,162 CNY and 5,748 CNY, respectively, while those with pneumonia are 6,096 CNY and 7,783 CNY. Patients from Shanghai, both bronchiolitis and pneumonia, exhibited the lowest cost expenditures, with average total costs of 3,531 CNY and 3,488 CNY, respectively. Multiple regression analysis indicated that, among bronchiolitis patients, factors such as region, medical insurance, relationship, loss of work time, and length of stay were found to be significantly associated with both hospitalization cost and total cost (P<0.05). For pneumonia patients, the hospitalization cost and total cost were significantly impacted by region, medical insurance, and length of stay (P<0.05). Conclusion: Bronchiolitis and pneumonia in children put substantial economic burden on families of affected children. The financial strain varies significantly across different regions, with families in underdeveloped areas and those dealing with pneumonia facing particularly daunting challenges. Targeted policies to reduce healthcare costs and improve insurance coverage, especially in economically disadvantaged regions are needed.